(untitled) (Research, Society and Development, 2020)
Persistence of the ductus arteriosus (PDA) is one of the congenital heart diseases that needs an immediate approach because it puts the life of the neonatal, commonly premature, at risk. This study aims to identify the nursing care performed by nurses in children with PDA and to compare the trajectory of nursing care to this population. A qualitative integrative descriptive review was carried out using a comparative history analysis. Four crosses of descriptors were used with the Boolean operator and on the website of the Virtual Health Library Brazil (VHL-Brazil) within the period from 1987 to 2017. As a result, five categories were obtained in which details about changes in pharmacological treatments and surgical procedures, nursing care, the clinical profile of these patients and nursing diagnoses. In addition to generating a nursing care assistance plan for children affected by this congenital heart disease. Through this research, it can be seen that there were changes in pharmacological and surgical treatments for these children affected by PDA. However, there were no significant changes for nursing care as they remained constant in view of the clinical profile of this.